The Role of Firms’ Life Cycle Stages on Voluntary Disclosure and Cost of Equity Capital in Brazilian Public Companies - Paulo Victor Novaes; Jose Elias Almeida (BBR: Brazilian Business Review)
We examine the effects of firms’ life cycle stages on voluntary disclosure and the cost of equity capital. We also examine the relationship between the interaction of life cycle stages and voluntary disclosures measures on cost of equity capital. Our sample consists of non-financial Brazilian public companies, covered by analysts between 2008 and 2014, collected from I/B/E/S and Comdinheiro databases. We find that voluntary disclosure level is higher for firms in maturity and growth stages. We also find that firms in introduction and decline life cycle stages show higher implied cost of capital, however declining firms that increase voluntary disclosure reduce their cost of capital. Moreover, mature firms significantly reduce such inherent risk by reporting social and environmental voluntary information. Our results are useful for investors, practitioners, and regulators to the understanding of the incentives of voluntary disclosure practices.